Simultaneous Assessment of Alogliptin Benzoate and Metformin Hydrochloride in Tablet Dosage Form by Reversed-phase High-performance Liquid Chromatography - Sen, Dr. Dhanya B. (Asian Journal of Pharmaceutics (AJP), 2022)
Aim: A simple, accurate, precise, and sensitive reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous assessment of alogliptin benzoate (ALO) and metformin hydrochloride (MET) in combined tablet formulation. Materials and Methods: The proposed RP-HPLC method employed a reverse phase column (C18) and mobile phase with a composition of 0.2% (v/v) triethylamine (pH 5.5 with orthophosphoric acid) and methanol (2:98, v/v) was utilized and a flow rate of1 mL min-1 was employed. Results and Discussion: Quantification of effluents was monitored at 236 nm. Three symmetrical well resolved peaks of alogliptin, metformin, and benzoic acid (benzoic acid was separated from ALO) were obtained with retention time of 4.730 ± 0.0267, 6.109 ± 0.0301, and 2.281 ± 0.0324 min, respectively. Both, alogliptin and metformin, showed excellent linearity over the concentration range of 0.5–50 μg mL-1. The developed method was, then, validated in accordance with ICH guidelines and applied in the determination of ALO and MET in the combined tablet dosage form. The formulation analysis revealed good agreement (98–100% w/w) with the label claim for both the analytes by RP-HPLC method. Conclusion: Developed method was simple, sensitive, and accurate which thus can be utilized for simultaneous determination of both the drugs in combined tablet dosage form.